1993
DOI: 10.1021/jo00067a019
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic approaches toward spiro[2,3-dihydro-4H-1-benzopyran-4,1'-cyclohexan]-2-one derivatives via radical reactions: total synthesis of (.+-.)-lycoramine

Abstract: Syntheses of spiro[2,3-dihydro-4H-l-benzopyran-4,l'-cyclohexan]-2-one derivatives by reaction sequences including a radical reaction and a total synthesis of (±)-lycoramine (2) are described. Radical reactions (BuaSnH, AIBN) of 1-[(l'-cyclohexenylmethyl)oxy] -2-halobenzenes 23b-d in boiling benzene gave the corresponding spiro[2,3-dihydrobenzofuran-3,l'-cyclohexanes] 26a,b in good yields, whereas the reaction of l-(l'-cyclohexenylethoxy)-2-bromobenzene (25) under similar conditions afforded a mixture of spiro[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…However, we found that this double bond installation was difficult to achieve. A simple method would be heating 7 with benzeneseleninic acid anhydride in toluene [9]. Under these conditions, we were able to synthesize a compound resulting from nucleophilic substitution of the anhydride with the enol of 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that this double bond installation was difficult to achieve. A simple method would be heating 7 with benzeneseleninic acid anhydride in toluene [9]. Under these conditions, we were able to synthesize a compound resulting from nucleophilic substitution of the anhydride with the enol of 7.…”
Section: Resultsmentioning
confidence: 99%
“…This ligand has unique structural features that are expected to be beneficial for improving enantioselectivities of some catalytic reactions. The key benzoferrocenyl building block (9) for the preparation of the ligand was synthesized stereoselectively. The aromatization of enantiopure 7 to benzoferrocene derivative 9 represents an unprecedented strategy for the synthesis of chiral ferrocenyl ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported failure in attempting 5-and 6-exo-trig radical ring closure of ester derivatives due to the geometric constraints associated with the preferred s-Z conformation of the ester function. [14][15][16][17][18][19][20] Thus, the successful Scheme. Reagents and conditions: i) I 2 , Ph 3 P, imidazole, toluene, reflux [70% (7) and 63% (8)]; ii) cinnamic acid or crotonic acid, DCC, DMAP, CH 2 Cl 2 , rt (56-79%).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is assumed that a fungus living in this plant 16 produced this compound. Meanwhile, a large number of such spiro compounds were isolated mostly from endophytic fungi and named diepoxines 1 , Sch plus number 8,17,18 , CJ-plus number 11 , cladosporins [19][20][21] , palmarumycins 3,[22][23][24] , sphaerolones 25 , decaspirones 4,17 and deoxypreussomerin 26 . The interesting structures, various biological activities and potential applications in agriculture, medicine and the food industry attracted the attention of many research groups with respect to the synthesis of spirobisnaphthalenes.…”
Section: Introductionmentioning
confidence: 99%